A mouthful - airway matters in intraoperative neuromonitoring in auditory brainstem implant surgery for the pediatric patient: a case series - Charis Khoo; A. H. NurHafiizhoh; Angela Tan; Tracy Tan; Hwan Ing Hee (BMC Anesthesiology, 2018)
Abstract Background The Auditory brainstem implant (ABI) is a new surgical option for hearing impaired children. Intraoperative neurophysiology monitoring includes brainstem mapping of cranial nerve (CN) IX, X, XI, XII and their motor nuclei, and corticobulbar tract motor-evoked potential. These require laryngeal electrodes and intra-oral pins, posing a challenge to airway management especially in the pediatric airway, where specialized electromyogram (EMG) tracheal tubes are not available. Challenges include determining the optimum position on the endotracheal tube (ETT) in which to place laryngeal electrode, and the increase in external diameter of ETT contributed by the wrapping the electrode around the shaft of ETT; this may necessitate downsizing of the tracheal tube. An appropriate size ETT minimizes displacement, which in turn can affect electrode contact with the vocal cords. Finally, a small thus crowded pediatric airway makes for difficult visualization during placement of intraoral neuromonitoring electrodes. The use of a videolaryngoscope helps determine optimum electrode placement. Case presentation We describe intraoperative neurophysiology monitoring and airway management for the first two ABI procedures in Singapore, conducted for children with congenitally absent cochlear nerves. Conclusion Neurophysiology cranial nerve IX, X, XII monitoring in the ABI procedure requires intraoral placement of electrodes. Care should be exercised during placement and removal. Vagus nerve monitoring in children requires attention to tube preparation, and consideration should be given to avoidance of airway topicalization.